Synthesis and characterization of novel aromatic-aliphatic polyamides from bis-[(4-aminobenzyl)-4-benzamide] ether - Patil, A. S.; Medhi, M.; Sadavarte, Nilakshi V.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A novel aromatic diamine monomer containing preformed aromatic-aliphatic amide and ether linkage, bis-[(4-aminobenzyl)-4-benzamide] ether (BABE) was prepared from 2-phenylacetonitrile. BABE was characterized by FT-IR, (1)H NMR, (13)C NMR and mass spectrometry. Five new aromatic polyamides were prepared by low temperature solution polymerization from BABE and different mole proportions of isophthaloyl chloride (IPC) or terephthaloyl chloride (TPC). The resulting polymers were characterized by means of FT-IR, inherent viscosity [eta(inh)], solubility, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA] and X-ray diffraction [XRD]. Polyamides were obtained in good yields and had moderate to high molecular weights as indicated by inherent viscosities in the range 0.63-1.35 dL/g in (DMAc + 4% LiCl). XRD results showed the partly crystalline nature of polymers and these polymers dissolved in aprotic polar solvents containing LiCl. The solubility of copolyamides improved due to random placement of constituent IPC and TPC during polymerization. DSC analysis of these polyamides showed glass transition temperatures in the range of 197-204 degrees C, and they showed no weight loss below 336 degrees C when analyzed by TG. These polyamides have potential applications as engineering materials. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bis-[(4-aminobenzyl)-4-benzamide] ether; ether linkage; Inherent viscosity; polyamides; thermal stability; XRD

Synthesis and characterization of polyamides containing pendant pentadecyl chains - More, Arvind S.; Pasale, Sharad K.; Wadgaonkar, Prakash P. (European Polymer Journal, 2010)
A new aromatic diacid monomer viz., 4-(4'-carboxyphenoxy)-2-pentadecylbenzoic acid was synthesized starting from cardanol and was characterized by FTIR, (1)H- and (13)C NMR spectroscopy. A series of new aromatic polyamides containing ether linkages and pendant pentadecyl chains was prepared by phosphorylation polycondensation of 4-(4'-carboxyphenoxy)-2-pentadecylbenzoic acid with five commercially available aromatic diamines viz., 1,4-phenylenediamine, 4,4'-oxydianiline, 4,4'-methylenedianiline, 1,3-phenylenediamine, and 4,4'-(hexafluoroisopropylidene)dianiline. Inherent viscosities of the polyamides were in the range 0.45-0.66 dL/g in N,N-dimethylacetamide at 30 +/- 0.1 degrees C. The introduction of ether linkages and pendant pentadecyl chains into polyamides led to an enhanced solubility in N,N-dimethylacetamide and 1-methyl-2-pyrrolidinone at room temperature or upon heating. The polyamides could be solution-cast into tough, flexible and transparent films from their N,N-dimethylacetamide solution. Wide angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were essentially amorphous in nature. X-Ray diffractograms also displayed a diffuse to sharp reflection in the small-angle region (20 = similar to 2-5 degrees) for the polyamides characteristics of formation of loosely to well-developed layered structure arising from packing of flexible pentadecyl chains. The glass transition temperature observed for the polyamides was in range 139-189 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of the polyamides was in the range 425-453 degrees C indicating their good thermal stability. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: alkyl side-chain; Cardanol; Cashew nut shell liquid; Pentadecyl chains; polyamides

Polyamides containing quinoxaline moiety - Patil, Vidyadhar B.; Sayyed, Maheboob M.; Mahanwar, Prakash A.; Wadgaonkar, Prakash P.; Maldar, Noormahamad N. (Journal of Polymer Research, 2011)
A new quinoxaline moiety containing aromatic diamine; 2,3-bis[4-(4-aminophenoxy)phenyl]quinoxaline (APQ) was synthesized starting from 4-methoxybenzaldehyde and was characterized by IR, (1)H, (13)C NMR and Mass spectrometry. Five new polyamides were synthesized by polycondensation of various aliphatic diacid / aromatic diacids namely, azelaic acid, bis(4-carboxyphenyl)dimethylsilane, 4,4'-oxybis(benzoicacid), isophthalic acid and terephthalic acid with APQ by Yamazaki's phosphorylation method using triphenyl phosphite as condensing agent. The polyamides were characterized by IR spectroscopy, solubility tests, inherent viscosity, X-ray diffraction technique, differential scanning colorimetry and thermogravimetric analysis. The polyamides had inherent viscosities in the range 0.39-0.45 dL/g in N, N-dimethylacetamide at 30 +/- 0.1 A degrees C. The polyamides were soluble in polar aprotic solvents such as N, N-dimethylacetamide, N, N-dimethylformamide, dimethylsulfoxide, N-methylpyrrolidone. X-Ray diffraction studies showed that polyamides were amorphous in nature. The polyamides showed glass transition temperatures in the range 104-205 A degrees C, according to differential scanning calorimetry. Thermogravimetric analysis exhibited initial decomposition temperatures above 348 A degrees C; indicating that these polyamides possessed excellent thermal stability.
Keywords: polyamides; Quinoxaline; solubility; Thermal properties; XRD

Synthesis and characterization of new organosoluble aromatic polyamides and polyazomethines containing pendent pentadecyl chains - Sadavarte, Nilakshi V.; Avadhani, C. V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2011)
New aromatic polyamides and polyazomethines containing pendent pentadecyl chains were synthesized by polycondensation of pentadecylbenzene-1,3-diamine with (i) four commercially available aromatic diacids, viz., biphenyl-4,4'dicarboxylic acid, 4,4'-oxybisbenzoic acid, terephthalic acid and isophthalic acid, and (ii) dialdehydes, viz., terephthaldehyde, isophthaldehyde and a 50 : 50 mol% mixture of terephthaldehyde, and isophthaldehyde, respectively. Inherent viscosities of polyamides and polyazomethines were in the range 0.35-0.56 dL g(-1) and 0.33-0.38 dL g(-1), respectively, indicating the formation of medium molecular weight polymers. The presence of pendent pentadecyl chains in polyamides and polyazomethines led to an improvement in their solubility in organic solvents. Polyamides could be cast into flexible, transparent and tough films from their solution in N,N-dimethylacetamide while polyazomethines could be solution cast into transparent, flexible and stretchable films from their CHCl(3) solution. (1)H-NMR studies based on amide proton signals and azomethine proton signals indicated the presence of constitutional isomerism in the polyamides and polyazomethines. Wide-angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were amorphous in nature. X-ray diffractograms also displayed sharp reflections in the small angle region (2 theta approximate to 3 degrees) indicating the formation of layered structure arising from packing of flexible pentadecyl chains. The glass transition (T(g)) temperatures of polyamides were in the range 169-215 degrees C while T(g) values for polyazomethines were in the range 16-55 degrees C. The temperature for the 10% weight loss of polyamides and polyazomethines were in the range 430-460 degrees C and 425-440 degrees C, respectively, in a nitrogen atmosphere, which indicated their good thermal stability. Polyazomethines were also characterized by UV-Vis and photoluminescence spectroscopy and optical band gap (E(g)) values, calculated according to the maximum of the UV absorption, were found to be in the range 2.82-3.10 eV.
Keywords: High performance polymers; optical band gap; polyamides; polyazomethines; solubility

Synergistic mechanical response of Nylon 6/Trogamid (R) T blends - Ridhore, Amol; Jog, Jyoti Prakash (Journal of Applied Polymer Science, 2013)
Blends of semicrystalline Nylon 6 with a varying ratios of amorphous Nylon are studied for their morphological, thermal, dielectric, and mechanical behavior. Thermal analysis indicated a compositional dependant decrease in the melting and crystallization temperatures of Nylon 6. The blends exhibited a single compositional dependant glass transition temperature in dynamic mechanical thermal analysis and dielectrical relaxation spectroscopy over entire mixing ratio indicating miscibility between the blend components. The values of flexural modulus and tensile modulus of the blends are found to increase without significant loss in the impact properties. The water absorption of the blends is also lower than the values calculated by rule of mixtures. The observed synergistic behavior of the mechanical properties of the blends is indicative of presence of strong interactions in the blends components. (c) 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013
Keywords: blends; dielectric properties; mechanical properties; polyamides; Thermal properties